Artificial Intelligence Applications and Learning Interest: A Case of Communication Science Students - Ahmat Anjani; Wafie Rahma Dewi; Zaskia Rochmani Putri; Yasqi Ikhwatuddin (Jurnal Komunikasi dan Bisnis, 2025)
The increasing use of Artificial Intelligence (AI) in higher education has brought notable changes to the way learning activities are designed and experienced, particularly through more interactive and individualized learning approaches. From a theoretical standpoint, AI-supported learning environments are assumed to foster greater student engagement and stimulate interest in the learning process. This study aims to investigate the influence of AI application usage on the learning interest of Communication Science students at a private university in Bandung. A quantitative research approach with an explanatory survey design was applied in this study. Data were obtained from 97 students through a structured online questionnaire and analyzed using simple linear regression techniques. The results show that AI application usage has a positive and statistically significant effect on students’ learning interest. Students who engage more frequently with AI-based tools tend to demonstrate higher levels of attention, enthusiasm, and inclination toward learning activities supported by AI. From a theoretical perspective, these findings contribute to the body of knowledge on technology-enhanced learning by reinforcing the role of AI in shaping students’ learning interests. From a practical perspective, the findings indicate that the thoughtful integration of AI-based tools into instructional practices can enhance student engagement and motivation to learn.